2022
DOI: 10.1186/s13046-022-02265-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel gene signature predicting response to first-line chemotherapy in BRCA wild-type high-grade serous ovarian cancer patients

Abstract: Background High-grade serous ovarian cancer (HGSOC) has poor survival rates due to a combination of diagnosis at advanced stage and disease recurrence as a result of chemotherapy resistance. In BRCA1 (Breast Cancer gene 1) - or BRCA2-wild type (BRCAwt) HGSOC patients, resistance and progressive disease occur earlier and more often than in mutated BRCA. Identification of biomarkers helpful in predicting response to first-line chemotherapy is a challenge to improve BRCAwt HGSOC management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…The experimental procedures related to primary cancer cell culture and characterization have been described previously [ 49 ]. Briefly, samples were collected at surgery from “leftover tissues” by using sterile scalpels.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental procedures related to primary cancer cell culture and characterization have been described previously [ 49 ]. Briefly, samples were collected at surgery from “leftover tissues” by using sterile scalpels.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, appropriate choice of cell lines for the different histotypes of EOC along with routine analysis of cell line authenticity are the first steps to increase the translational value of cell line studies in preclinical research on EOC. Besides, our and literature data have also demonstrated that established EOC cell lines, although easier to work with than primary cells, may not be recommended to understand determinants of sensitivity to current therapies or to translate novel therapies into the clinics [ 6 , 175 ]. These models, however, under the right conditions and with the appropriate controls, retain their utility in mechanistic work at the protein and pathway level (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, primary tumour cell cultures more closely resemble the patient situation, and therefore, they represent a more experimentally accurate model for the reproduction of cancer in in vitro systems. Due to these unique features, they are a valuable experimental tool during preclinical studies of drug resistance mechanisms, as we also recently demonstrated [ 175 ]. However, the need of characterization for determining origin and purity, the limited lifespan of days or weeks, and the slow growth, constitute important limitations to their use (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that patients with the same histology and TNM stages may have very distinct clinical outcomes, mainly due to their genetic heterogeneities ( 20 ). With the rapid development of the next-generation sequencing, a growing number of prognostic signatures based on transcriptome data were established to depict the individual differences, and to forecast the prognosis in various cancers ( 21 23 ). Therefore, a more reliable prognostic model based on genetic alterations is urgently needed to provide early detection and personalized treatment for LUAD patients.…”
Section: Discussionmentioning
confidence: 99%